Modelling and optimization of tool life in end milling of AISI 02 hardened steel - Lajis, M. A.; Karim, A.N. Mustafizul; Amin, A. K. M. Nurul (2008)
Majority of the published research works on modeling of tool life in machining of hardened steels are based mainly on the turning process, whilst the hard milling process has rarely been adopted. This work is aimed to determine the optimum cutting condltlons leading to maximum tool life in end miling of AISI 02 hardened steel using PVD TIAIN coated carbide tool Inserts usinq first and second order models. Analysis of variance (ANOVA) has been conducted for both the models to check the adequacy levels. It has been found that the models are valid for predicting the tool life in machining under specified condition with an average of error less than 10%.